Um passeio pelo bariloche de 1917. Uma exposição para pensar a arqueologia - Fernández Do Rio, Solange; Murriello, Sandra (InMediaciones de la Comunicación, 2018)
The communication of science in museums responds to communication models, either implicitly or explicitly, that assign certain roles to visitors and curators, that entail a position and an understanding about the knowledge status being constructed in the museum space. The process of development of the exhibition Walking around Bariloche in 1917: a tour that join together fragments, stories and institutions, was created in 2017 at the Museum de la Patagonia (city of Bariloche, Rio Negro Province, Argentina). The exhibition confronted us to the challenge of revealing the way in which urban historical Archaeology works. To this purpose, was designed an approach that interpellates the visitors through diverse museographic resources, with few objects and an emphasis in interpretative charts. We adhere to the idea of a model of museum, which enables an active search for sharing power with the community understanding the “museological” phenomenon as a production of meanings through the ordering, conjugation and structuring of the elements of the proposed exhibition.